MARIE CLAIRE e SOU MAIS EU: figurativizações do belo feminino - Raiz, Amanda Cristina Martins (2010)
Attempting to find a meaning to his life, the human being notices is necessary to interact to other people. Thus, he tends to recognize not only the other’s behavior, habits and tastes which are similar to his but also those which are different. Therefore, the social interaction is based on identities and alterities. In Presenças do outro, Landowski (2001) presents the semiotization of the social behavior. There are several groups in the society, which members remain there considering their affinities. In this moment the differences are also recognized and the meaning comes about. The theoretical methodology of French Semiotics was developed to think about the structuration and organization of the texts. Consequently, it is possible to say the French Semiotics studies questions which are concerned to the way of texts are articulated. In other words, the French Semiotics tries to say how a text makes to say what it says. Trying to understand the meaning of the term “modern/contemporary woman”, our major purpose was to verify how that term is figurativized in two female magazines – Marie Claire and Sou mais eu –, in order to comprehend the notion of the qualificative term “modern” and the possibility of its comprehension as a synonym of contemporary. In view of the fact the periodics we analised are toward to people whose social position are different, we verified there are also different conceptions to the term “beautiful” because we can see pictures of great beautiful female icons see in the texts of both magazines. Our research was based on the French Semiotics but we enfasize the studies of Sociossemiotics, mainly the studies developed by Eric Landowski. Motivated by the thought of Landowski (2001), whose studies of semiotization of the social exclusion behavior of members who are not similar to those who belong to the referential groups, we can prove the necessity of someone conform his behavior in order to belong to referential groups. Therefore, the study of the contemporary beauty is relevant to demonstrate how the anatomic and fisionomic aesthetics of our time are because it is a historical registration to the future generations.